Back Cover: A green ultra‐fast liquid chromatographic method for quantification of curcumin in extract of Curcuma longa L. followed by confirmation via spectroscopic techniques. Issue 3 (4th March 2021) - Ahmed, Mahmood; Ahmad, Saghir; Irfan, Masooma
Abstract : DOI: 10.1002/sscp.202000063 The cover picture shows the separation of curcuminoids from extract of Curcuma longa L by using ultra‐fast liquid chromatography.